Efeito da palpação retal e da frequencia de inseminações na fertilidade de éguas inseminadas com sêmen fresco diluído - Silva, J. M.; Fonseca, F. A.; Carvalho, G. R.; Palhares, M. S.; Motta, VAF; Oliveira, H. N. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1997)
Forty-two mares were randomly assigned in a 3 x 2 factorial experiment which included three intervals between rectal palpation (6/6h, 12/12h and once a day palpation) and two frequencies of inseminations (daily or every other day). The mares were inseminated with semen from only one stallion, diluted in minimal contamination extender. There were no differences in the conception rate at first cycle, conception/cycle, conception total, efficiency of pregnancy in either system of rectal palpation, independently of the frequency of insemination utilized. Also there were no differences among intervals of rectal palpation concerning the following reproductive characteristics: number of cycles/mare, cycles/pregnant mare, cycles/ pregnancy, pregnancy/cycle, number of inseminations/mare, inseminations/ pregnant mare and insemination/open mare. There were no differences in pregnancy rate at first cycle, pregnancy rate/cycle, pregnancy rate total and efficiency of pregnancy between the two frequency of insemination. However, the frequency of insemination influenced the number of inseminations/mare, number of inseminations/ pregnant mare and inseminations/open mare. The highest values were observed with the mares inseminated daily. Therefore, insemination every other day can be recommended. If necessary the mare may be palpated rectally at intervals of six hours without reducing the pregnancy rate.
Effect of rectal palpation and frequency of inseminations on fertility of inseminated mares with fresh diluted semen
Keywords: artificial insemination; rectal palpation; mare